A high polymer nano-memory rubber-based self-repairing tire and a preparation method thereof
Patent Information
- Application Number
- CN202611175640.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-27
AI Technical Summary
现有方案若通过提高胶料黏度、内聚强度或交联程度增强运行状态下的结构稳定性,通常会增加高温输送和喷涂阻力,并可能限制低温下胶料向刺孔区域的回填;若通过增加液体橡胶、增塑剂等软化组分改善喷涂流动性和低温回填能力,又容易削弱胶层在运行温度及离心载荷下的尺寸稳定性
本发明通过在聚丁二烯接枝纳米二氧化硅表面同时构建脲基嘧啶酮缔合端基和烷基封闭端基,形成兼具橡胶相容性、可逆缔合能力和界面稳定性的混合端基型纳米改性物质。聚丁二烯链段及烷基封闭端基能够改善纳米颗粒在非极性橡胶基体中的分散状态,减少颗粒团聚及极性位点局部富集;脲基嘧啶酮缔合端基则可在轮胎运行温度下形成可逆物理缔合结构,使自密封材料在受到高剪切或周期形变后恢复内部结构。通过将所述纳米改性物质预先分散于液体橡胶和部分增塑剂中,再与热塑性弹性体、聚异丁烯及增粘树脂熔融复合,本发明在保持高温输送和喷涂流动性的同时,提高了自密封层在运行温度及离心载荷下的结构恢复能力和抗迁移性能,并避免因过度提高黏度或化学交联程度而明显削弱低温刺孔回填能力,实现了喷涂加工性、运行稳定性和低温自密封性能的协调统一。
Smart Images

Figure CN122976084A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of tire technology, and in particular to a self-healing tire based on polymer nano-memory rubber and its preparation method. Background Technology
[0002] With the increasing demands for high-speed, heavy-duty, and long-distance vehicle operation, the problem of continuous air leakage caused by tire punctures from nails or sharp foreign objects is receiving growing attention. Existing technologies typically incorporate a rubber-based self-sealing layer on the inner wall of a vulcanized tubeless tire, corresponding to the tread area. This self-sealing layer is generally formed by melt-mixing components such as thermoplastic elastomers, polyisobutylene, liquid rubber, tackifying resin, plasticizers, and antioxidants, followed by hot-melt spraying or coating. When a foreign object punctures the tire, the self-sealing material encapsulates the object and fills the gap between it and the puncture. After the object is removed, the self-sealing material deforms and refills the puncture area under the tire's internal pressure and its own viscoelasticity, thereby delaying or preventing gas leakage. Current research primarily focuses on improving the material's hot-melt processability, puncture sealing, and dimensional stability of the rubber layer by adjusting the molecular weight of the main elastomer, the amount of tackifying resin and plasticizer, the thickness of the rubber layer, the spraying temperature, and the tire rotation conditions. However, rubber-based self-sealing materials need to meet mutually restrictive performance requirements during processing, layering, and tire use. During high-temperature conveying and spraying, the material needs suitable melt flowability to smoothly pass through the feeding and spraying devices and form a continuous, uniform self-sealing layer. Under tire operating temperatures, cyclic deformation, and centrifugal loads, the self-sealing layer needs sufficient yield strength and structural resilience to avoid circumferential or axial migration, sagging, and localized accumulation. When a tire is punctured at low temperatures, the material must also maintain localized deformation and puncture backfilling capability. Existing solutions that enhance structural stability under operating conditions by increasing rubber viscosity, cohesive strength, or cross-linking degree typically increase high-temperature conveying and spraying resistance and may limit the backfilling of the rubber compound into the puncture area at low temperatures. Conversely, improving spray flowability and low-temperature backfilling capability by adding softening components such as liquid rubber and plasticizers can easily weaken the dimensional stability of the rubber layer under operating temperatures and centrifugal loads. Therefore, how to improve the structural stability of rubber-based self-sealing materials under tire operating temperature and centrifugal load while maintaining the fluidity of high-temperature transportation and spraying, and at the same time avoid reducing the low-temperature puncture backfilling capacity due to increasing the cohesive strength or cross-linking degree of the rubber compound, remains a problem that needs to be solved by existing technologies. Summary of the Invention
[0003] To address the above problems, this invention proposes a polymer nano-memory rubber-based self-healing tire and its preparation method. This invention can be achieved through the following technical solutions: A method for preparing a polymer nano-memory rubber-based self-healing tire includes the following steps: S1. Nano-silica is reacted with aminosilane in an alcohol-water medium to obtain aminated nano-silica; the aminated nano-silica is then reacted with diisocyanate to obtain isocyanate-functionalized nano-silica; hydroxyl-terminated liquid polybutadiene is added to perform a grafting reaction at a molar ratio of (3-6):1 between the hydroxyl groups in the hydroxyl-terminated liquid polybutadiene and the isocyanate groups in the isocyanate-functionalized nano-silica; unreacted hydroxyl-terminated liquid polybutadiene is removed by separation to obtain polybutadiene with hydroxyl-terminated ends. olefin-grafted nano-silica; according to the molar ratio of isocyanate groups to terminal hydroxyl groups in the isocyanate-containing ureapyrimidine ketone compound being (0.20~0.50):1, an isocyanate-containing ureapyrimidine ketone compound is added for reaction, and then according to the molar ratio of isocyanate groups in the alkyl monoisocyanate to the remaining terminal hydroxyl groups after the reaction being (1.0~1.1):1, an alkyl monoisocyanate is added for end-capping reaction, to obtain a mixed-terminal type nano-modified material containing both ureapyrimidine ketone associated end groups and alkyl-capped end groups; S2. The mixed end-group type nano-modified material is added to liquid rubber and part of plasticizer for pre-dispersion to obtain nano-modified pre-dispersion. Then, the nano-modified pre-dispersion is melt-composite with thermoplastic elastomer, polyisobutylene, tackifying resin, remaining plasticizer and antioxidant to obtain rubber-based self-sealing material. S3. Clean and preheat the inner wall of the vulcanized tire, heat the rubber-based self-sealing material to a flowable state, and spray it onto the area of the inner wall of the vulcanized tire corresponding to the tread. S4. Keep the sprayed vulcanized tire rotating and cool it to set, forming a continuous rubber-based self-sealing layer on the inner wall of the vulcanized tire, thus obtaining a polymer nano-memory rubber-based self-healing tire.
[0004] Preferably, in S1, the average particle size of the nano-silica is 10–80 nm; the aminosilane is selected from 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane; the mass ratio of the nano-silica to the aminosilane is 100:(3–12); the mass ratio of ethanol to water in the alcohol-water medium is (80–95):(5–20); the pH of the reaction system is 3.5–5.0; the reaction temperature is 60–75 °C; and the reaction time is 3–6 h.
[0005] Preferably, in S1, the diisocyanate is selected from isophorone diisocyanate, hexamethylene diisocyanate, and dicyclohexylmethane diisocyanate; the molar ratio of the isocyanate group in the diisocyanate to the amino group in the aminated nano silica is (2.2-3.5):1, the reaction temperature is 40-55℃, and the reaction time is 2-4 h.
[0006] Preferably, in step S1, the number-average molecular weight of the hydroxyl-terminated liquid polybutadiene is 1000–5000, and the average hydroxyl functionality is 1.8–2.6. The grafting reaction is carried out in an anhydrous organic solvent and under a protective atmosphere, at a reaction temperature of 55–75°C, for a reaction time of 8–12 h, and an organotin catalyst of 0.05%–0.30% of the total mass of the reactants in this step is added. After the grafting reaction is completed, the reaction product is washed with butyl acetate to remove unreacted hydroxyl-terminated liquid polybutadiene.
[0007] Preferably, in S1, the isocyanate-containing ureidopyrimidinone compound is prepared by reacting 2-amino-4-hydroxy-6-methylpyrimidine with diisocyanate at a molar ratio of 1:(5-8) under a protective atmosphere and at 100-110°C for 12-18 h, followed by precipitation, separation, washing and drying.
[0008] Preferably, in step S1, the hydroxyl-terminated polybutadiene-grafted nano-silica reacts with the isocyanate-containing ureidopyrimidinone compound at 30–50°C for 12–24 h, and an organotin catalyst comprising 0.10%–0.50% of the total mass of the reactants in this step is added; the alkyl monoisocyanate is selected from one of n-octyl isocyanate, dodecyl isocyanate, and octadecyl isocyanate; the end-capping reaction is carried out at a temperature of 45–65°C for a reaction time of 3–6 h.
[0009] Preferably, by weight, the raw materials for preparing the rubber-based self-sealing material in S2 include: 15-35 parts of thermoplastic elastomer, 20-45 parts of polyisobutylene, 10-30 parts of liquid rubber, 15-35 parts of tackifying resin, 5-20 parts of plasticizer, 1-6 parts of mixed end-group nano-modified material, and 0.2-1.5 parts of antioxidant; the thermoplastic elastomer is selected from one or two of styrene-isoprene-styrene block copolymer, styrene-butadiene-styrene block copolymer, and styrene-ethylene / butene-styrene block copolymer; the liquid rubber is selected from one of liquid polyisoprene and liquid polybutadiene.
[0010] Preferably, the tackifying resin is selected from one or two of hydrogenated petroleum resin, terpene resin, and hydrogenated rosin resin; the plasticizer is selected from one of naphthenic oil and paraffin oil; and the antioxidant is selected from one of hindered phenolic antioxidant and phosphite antioxidant. In S2, the plasticizer used for pre-dispersion accounts for 20% to 50% of the total mass of the plasticizer, the pre-dispersion temperature is 70 to 110°C, and the pre-dispersion time is 15 to 45 min. The melt composite temperature is 120 to 170°C, and the time is 10 to 40 min.
[0011] Preferably, in step S3, the spraying temperature of the rubber-based self-sealing material is 130–190°C, the preheating temperature of the inner wall of the vulcanized tire is 35–70°C, and the rotation speed of the vulcanized tire during the spraying process is 5–30 r / min; the thickness of the rubber-based self-sealing layer obtained in step S4 is 2.0–5.0 mm, and the coverage width is 80%–120% of the designed tread width of the vulcanized tire.
[0012] The beneficial effects of this invention are: This invention constructs ureidopyrimidinone associative end groups and alkyl-closed end groups simultaneously on the surface of polybutadiene grafted with nano-silica, forming a hybrid-end-group type nano-modified material that combines rubber compatibility, reversible association ability, and interfacial stability. The polybutadiene segments and alkyl-closed end groups improve the dispersion of nanoparticles in a non-polar rubber matrix, reducing particle agglomeration and local enrichment at polar sites. The ureidopyrimidinone associative end groups can form a reversible physical association structure at tire operating temperatures, allowing the self-sealing material to recover its internal structure after being subjected to high shear or cyclic deformation. By pre-dispersing the nano-modified material in liquid rubber and a portion of the plasticizer, and then melt-compositing it with thermoplastic elastomers, polyisobutylene, and tackifying resins, this invention maintains high-temperature transport and spraying fluidity while improving the structural recovery ability and anti-migration performance of the self-sealing layer under operating temperatures and centrifugal loads. It also avoids significantly weakening the low-temperature pore-filling ability due to excessively increased viscosity or chemical cross-linking, achieving a harmonious balance between spraying processability, operational stability, and low-temperature self-sealing performance. Attached Figure Description
[0013] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used in conjunction with embodiments of the invention to explain the invention and do not constitute a limitation thereof. In the drawings: Figure 1 These are the results of core performance tests on the tire. Detailed Implementation
[0014] The following provides a detailed description of the embodiments of the present invention: These embodiments are implemented based on the technical solution of the present invention, and provide detailed implementation methods and processes. However, the scope of protection of the present invention is not limited to the following embodiments. Experimental methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions.
[0015] Common operating conditions for the examples: In the following examples, unless otherwise stated, the nano-silica was dried for 3 h at 110°C and a vacuum of -0.09 MPa before use; reactions involving isocyanate groups were carried out under nitrogen protection, with a stirring speed of 500 r / min and a dropwise addition time of 30 min for liquid reactants. The amination reaction product was washed with ethanol, and the remaining intermediates were washed with butyl acetate; each intermediate was centrifuged at 8000 r / min for 10 min, washed 3 times, and dried for 12 h at 50°C and a vacuum of -0.09 MPa. The following examples used 205 / 55R16 tubeless radial tires of the same specifications; the inner wall of the tire was wiped 3 times with isopropanol and air-dried for 30 min. The nozzle diameter of the spraying equipment is 1.8 mm, the spraying pressure is 0.6 MPa, the distance between the nozzle and the inner wall of the tire is 100 mm, and the axial movement speed of the nozzle is 40 mm / s. After spraying, the tire is cooled with air at 25℃ and then left to stand at 23±2℃ for 24 h.
[0016] Functional group determination and feed calculation methods: The amino content of aminated nano-silica was determined by acid-base back titration; the isocyanate group content of isocyanate-functionalized nano-silica and isocyanate-containing ureidopyrimidinone compounds was determined by di-n-butylamine back titration; and the terminal hydroxyl content of polybutadiene-grafted nano-silica was calculated based on the hydroxyl value determination results. The functional group molar ratios mentioned in the examples were calculated based on the measured functional group content of the corresponding intermediate products.
[0017] Example 1: A method for preparing a polymer nano-memory rubber-based self-healing tire, comprising the following steps: S1. 100 g of nano-silica with an average particle size of 10 nm was dispersed in an alcohol-water medium composed of 800 g of ethanol and 200 g of water. The pH of the system was adjusted to 3.5, and 3 g of 3-aminopropyltriethoxysilane was added. The mixture was reacted at 60 °C for 3 h. After separation, washing, and drying, aminated nano-silica was obtained. Based on the measured amino content, 24.45 g of isophorone diisocyanate was added to the aminated nano-silica containing 0.100 mol of amino groups, making the molar ratio of isocyanate groups to amino groups 2.2:1. The mixture was reacted at 40 °C for 2 h to obtain isocyanate-functionalized nano-silica. 16.67 g of isocyanate-functionalized nano-silica containing 0.010 mol of isocyanate groups was added to the isocyanate-functionalized nano-silica. Hydroxyl-terminated liquid polybutadiene with a number-average molecular weight of 1000 and an average hydroxyl functionality of 1.8 was mixed with 0.05% dibutyltin dilaurate. The mixture was reacted at 55°C for 8 h. After separation and washing away unreacted hydroxyl-terminated liquid polybutadiene, hydroxyl-terminated polybutadiene-grafted nano-silica was obtained. 12.51 g of 2-amino-4-hydroxy-6-methylpyrimidine and 111.15 g of isophorone diisocyanate were mixed at a molar ratio of 1:5 and reacted at 100°C for 12 h. After precipitation with n-hexane, separation, washing, and drying, a ureidopyrimidinone compound containing isocyanate groups was obtained. 0.010 mol of hydroxyl-terminated polybutadiene-grafted nano-silica was added to the mixture containing 0.0020 mol of dibutyltin dilaurate. A ureidopyrimidinone compound with isocyanate groups was prepared, with a molar ratio of isocyanate groups to terminal hydroxyl groups of 0.20:1. Dibutyltin dilaurate was added at 0.10% of the total mass of the reactants in this step, and the reaction was carried out at 30°C for 12 h. Based on the measured residual hydroxyl content, dodecyl isocyanate was added at a molar ratio of isocyanate groups to residual hydroxyl groups of 1.0:1, and the reaction was carried out at 45°C for 3 h. After separation, washing, and drying, a mixed-terminated nano-modified material was obtained. S2. Weigh 150 g of styrene-isoprene-styrene block copolymer, 200 g of polyisobutylene, 100 g of liquid polyisoprene, 150 g of hydrogenated petroleum resin, 50 g of naphthenic oil, 10 g of mixed end-group nano-modifier, and 2 g of antioxidant 1010. Take 20% of the total mass of naphthenic oil, i.e., 10 g, and mix it with liquid polyisoprene and mixed end-group nano-modifier. Pre-disperse at 70°C for 15 min to obtain a nano-modified pre-dispersion. Mix the nano-modified pre-dispersion with styrene-isoprene-styrene block copolymer, polyisobutylene, hydrogenated petroleum resin, the remaining 40 g of naphthenic oil, and antioxidant 1010. Melt composite at 120°C for 10 min to obtain a rubber-based self-sealing material. S3. Preheat the cleaned vulcanized tire inner wall to 35°C, heat the rubber-based self-sealing material to 130°C, rotate the tire at a speed of 5 r / min, and spray the rubber-based self-sealing material onto the area of the tire inner wall corresponding to the tread. S4. After spraying, keep the tire rotating and air-cooled until the inner wall temperature of the tire drops below 40°C, forming a rubber-based self-sealing layer with a thickness of 2.0 mm and a coverage width of 80% of the designed tread width of the vulcanized tire, thus obtaining a polymer nano-memory rubber-based self-healing tire.
[0018] Example 2: A method for preparing a polymer nano-memory rubber-based self-healing tire, comprising the following steps: S1. 100 g of nano-silica with an average particle size of 45 nm was dispersed in an alcohol-water medium composed of 875 g of ethanol and 125 g of water. The pH of the system was adjusted to 4.25, and 7.5 g of 3-aminopropyltriethoxysilane was added. The mixture was reacted at 67.5 °C for 4.5 h. After separation, washing, and drying, aminated nano-silica was obtained. Based on the measured amino content, 0.100 mol of aminated nano-silica containing amino groups was taken, and 31.68 g of isophorone diisocyanate was added to make the molar ratio of isocyanate groups to amino groups 2.85:1. The mixture was reacted at 47.5 °C for 3 h to obtain isocyanate-functionalized nano-silica. 0.010 mol of isocyanate-functionalized nano-silica containing isocyanate groups was added to 61.36 g of isophorone diisocyanate. Hydroxyl-terminated liquid polybutadiene with a number-average molecular weight of 3000 and an average hydroxyl functionality of 2.2 was mixed with 0.175% dibutyltin dilaurate. The mixture was reacted at 65°C for 10 h. After separation and washing to remove unreacted hydroxyl-terminated liquid polybutadiene, hydroxyl-terminated polybutadiene-grafted nano-silica was obtained. 12.51 g of 2-amino-4-hydroxy-6-methylpyrimidine and 144.49 g of isophorone diisocyanate were mixed at a molar ratio of 1:6.5 and reacted at 105°C for 15 h. After precipitation with n-hexane, separation, washing, and drying, a ureidopyrimidinone compound containing isocyanate groups was obtained. 0.010 mol of hydroxyl-terminated polybutadiene-grafted nano-silica was added to the mixture containing 0.0035 mol of dibutyltin dilaurate. A ureidopyrimidinone compound with isocyanate groups was prepared, with a molar ratio of isocyanate groups to terminal hydroxyl groups of 0.35:1. Dibutyltin dilaurate was added at 0.30% of the total mass of the reactants in this step, and the reaction was carried out at 40°C for 18 h. Based on the measured residual hydroxyl content, dodecyl isocyanate was added at a molar ratio of isocyanate groups to residual hydroxyl groups of 1.05:1, and the reaction was carried out at 55°C for 4.5 h. After separation, washing, and drying, a mixed-terminated nano-modified material was obtained. S2. Weigh 250 g of styrene-isoprene-styrene block copolymer, 325 g of polyisobutylene, 200 g of liquid polyisoprene, 250 g of hydrogenated petroleum resin, 125 g of naphthenic oil, 35 g of mixed end-group nano-modifier, and 8.5 g of antioxidant 1010; take 35% of the total mass of naphthenic oil, i.e., 43.75 g, and mix it with liquid polyisoprene and mixed end-group nano-modifier, and pre-disperse it at 90℃ for 30 min to obtain a nano-modified pre-dispersion; mix the nano-modified pre-dispersion with styrene-isoprene-styrene block copolymer, polyisobutylene, hydrogenated petroleum resin, the remaining 81.25 g of naphthenic oil and antioxidant 1010, and melt-composite it at 145℃ for 25 min to obtain a rubber-based self-sealing material; S3. Preheat the cleaned vulcanized tire inner wall to 52.5℃, heat the rubber-based self-sealing material to 160℃, rotate the tire at a speed of 17.5 r / min, and spray the rubber-based self-sealing material onto the area of the tire inner wall corresponding to the tread. S4. After spraying, keep the tire rotating and air-cooled until the inner wall temperature of the tire drops below 40°C, forming a rubber-based self-sealing layer with a thickness of 3.5 mm and a coverage width of 100% of the designed tread width of the vulcanized tire, thus obtaining a polymer nano-memory rubber-based self-healing tire.
[0019] Example 3: A method for preparing a polymer nano-memory rubber-based self-healing tire, comprising the following steps: S1. 100 g of nano-silica with an average particle size of 80 nm was dispersed in an alcohol-water medium consisting of 950 g of ethanol and 50 g of water. The pH of the system was adjusted to 5.0, and 12 g of 3-aminopropyltriethoxysilane was added. The mixture was reacted at 75 °C for 6 h. After separation, washing, and drying, aminated nano-silica was obtained. Based on the measured amino content, 0.100 mol of amino groups in the aminated nano-silica was taken, and 38.90 g of isophorone diisocyanate was added to make the molar ratio of isocyanate groups to amino groups 3.5:1. The mixture was reacted at 55 °C for 4 h to obtain isocyanate-functionalized nano-silica. 0.010 mol of isocyanate-functionalized nano-silica was taken, and 115.38 g of isocyanate diisocyanate was added to the mixture. Hydroxyl-terminated liquid polybutadiene with a number-average molecular weight of 5000 and an average hydroxyl functionality of 2.6 was mixed with 0.30% dibutyltin dilaurate. The mixture was reacted at 75°C for 12 h. After separation and washing away unreacted hydroxyl-terminated liquid polybutadiene, hydroxyl-terminated polybutadiene-grafted nano-silica was obtained. 12.51 g of 2-amino-4-hydroxy-6-methylpyrimidine and 177.83 g of isophorone diisocyanate were mixed at a molar ratio of 1:8 and reacted at 110°C for 18 h. After precipitation with n-hexane, separation, washing, and drying, a ureidopyrimidinone compound containing isocyanate groups was obtained. 0.010 mol of hydroxyl-terminated polybutadiene-grafted nano-silica was added to the mixture containing 0.0050 mol of dibutyltin dilaurate. A ureidopyrimidinone compound with isocyanate groups was prepared, with a molar ratio of isocyanate groups to terminal hydroxyl groups of 0.50:1. Dibutyltin dilaurate was added at 0.50% of the total mass of the reactants in this step, and the reaction was carried out at 50°C for 24 h. Based on the measured residual hydroxyl content, dodecyl isocyanate was added at a molar ratio of isocyanate groups to residual hydroxyl groups of 1.1:1, and the reaction was carried out at 65°C for 6 h. After separation, washing, and drying, a mixed-terminated nano-modified material was obtained. S2. Weigh out 350 g of styrene-isoprene-styrene block copolymer, 450 g of polyisobutylene, 300 g of liquid polyisoprene, 350 g of hydrogenated petroleum resin, 200 g of naphthenic oil, 60 g of mixed end-group nano-modifier, and 15 g of antioxidant 1010; take 50% of the total mass of naphthenic oil, i.e., 100 g, and mix it with liquid polyisoprene and mixed end-group nano-modifier, and pre-disperse it at 110℃ for 45 min to obtain a nano-modified pre-dispersion; mix the nano-modified pre-dispersion with styrene-isoprene-styrene block copolymer, polyisobutylene, hydrogenated petroleum resin, the remaining 100 g of naphthenic oil, and antioxidant 1010, and melt-composite it at 170℃ for 40 min to obtain a rubber-based self-sealing material; S3. Preheat the cleaned vulcanized tire inner wall to 70°C, heat the rubber-based self-sealing material to 190°C, rotate the tire at a speed of 30 r / min, and spray the rubber-based self-sealing material onto the area of the tire inner wall corresponding to the tread. S4. After spraying, keep the tire rotating and air-cooled until the inner wall temperature of the tire drops below 40°C, forming a rubber-based self-sealing layer with a thickness of 5.0 mm and a coverage width of 120% of the designed tread width of the vulcanized tire, thus obtaining a polymer nano-memory rubber-based self-healing tire.
[0020] Comparative Example 1: The difference between this comparative example and Example 1 is that the mixed end-group modified nanomaterial is not prepared, and the mixed end-group modified nanomaterial in Example 1 is replaced with an equal mass of unmodified nano silica.
[0021] The method for preparing the self-healing tire in this comparative example includes the following steps: S1. Dry nano-silica with an average particle size of 10 nm at 110 °C and a vacuum of -0.09 MPa for 3 h to obtain dried nano-silica. S2. Weigh 150 g of styrene-isoprene-styrene block copolymer, 200 g of polyisobutylene, 100 g of liquid polyisoprene, 150 g of hydrogenated petroleum resin, 50 g of naphthenic oil, 10 g of dry nano-silica, and 2 g of antioxidant 1010; take 20% of the total mass of naphthenic oil, i.e., 10 g, and mix it with liquid polyisoprene and dry nano-silica, and pre-disperse it at 70℃ and 1000 r / min for 15 min to obtain a nano-predispersed body; mix the nano-predispersed body with styrene-isoprene-styrene block copolymer, polyisobutylene, hydrogenated petroleum resin, the remaining 40 g of naphthenic oil, and antioxidant 1010, and melt-composite it at 120℃ and 60 r / min for 10 min to obtain a rubber-based self-sealing material; S3. Preheat the inner wall of the cleaned 205 / 55R16 tubeless radial tire to 35°C, heat the rubber-based self-sealing material to 130°C, rotate the tire at a speed of 5 r / min, and spray the rubber-based self-sealing material onto the area of the inner wall of the tire corresponding to the tread. S4. After spraying, the tire continues to rotate and is cooled by air to form a rubber-based self-sealing layer with a thickness of 2.0 mm and a coverage width of 80% of the designed tread width of the vulcanized tire, thus obtaining a polymer nano-memory rubber-based self-healing tire.
[0022] Comparative Example 2: The difference between this comparative example and Example 1 is that the preparation process of the mixed end-group type nano-modified material is terminated after the hydroxyl-terminated liquid polybutadiene grafting is completed, and the ureidopyrimidinone end-grouping reaction and dodecyl isocyanate end-grouping reaction are no longer carried out. The resulting polybutadiene-grafted nano-silica with hydroxyl-terminated ends is used instead of the mixed end-group type nano-modified material in Example 1.
[0023] The method for preparing the self-healing tire in this comparative example includes the following steps: S1. 100 g of nano-silica with an average particle size of 10 nm was dispersed in an alcohol-water medium composed of 800 g of ethanol and 200 g of water. The pH of the system was adjusted to 3.5, and 3 g of 3-aminopropyltriethoxysilane was added. The mixture was reacted at 60 °C for 3 h. After separation, washing, and drying, aminated nano-silica was obtained. Based on the measured amino content, 24.45 g of isophorone diisocyanate was added to the aminated nano-silica containing 0.100 mol of amino groups, making the molar ratio of isocyanate groups to amino groups 2.2:1. The mixture was reacted at 40 °C for 2 h to obtain isocyanate-functionalized nano-silica. 16.67 g of isocyanate-functionalized nano-silica containing 0.010 mol of isocyanate groups was added to the isocyanate-functionalized nano-silica. Hydroxyl-terminated liquid polybutadiene with a number average molecular weight of 1000 and an average hydroxyl functionality of 1.8 was prepared, with a molar ratio of hydroxyl to isocyanate groups of 3:1. Dibutyltin dilaurate was added at 0.05% of the total mass of the reactants in this step. The reaction was carried out at 55°C for 8 h. After separating and washing away the unreacted hydroxyl-terminated liquid polybutadiene, hydroxyl-terminated polybutadiene-grafted nano-silica was obtained. S2. Weigh 150 g of styrene-isoprene-styrene block copolymer, 200 g of polyisobutylene, 100 g of liquid polyisoprene, 150 g of hydrogenated petroleum resin, 50 g of naphthenic oil, 10 g of hydroxyl-terminated polybutadiene-grafted nano silica, and 2 g of antioxidant 1010; the pre-dispersion and melt composite operations, as well as the tire inner wall spraying and cooling shaping operations, are all carried out according to Example 1 to obtain a polymer nano-memory rubber-based self-healing tire.
[0024] Comparative Example 3: The difference between this comparative example and Example 1 is that the ureidopyrimidinone associative end group and the alkyl blocked end group are respectively set on the surface of different polybutadiene-grafted nano silica particles, and then the two types of single-end-group nano-modified materials are physically mixed; in Example 1, the two types of end groups are simultaneously set on the surface of the same nanoparticle.
[0025] The method for preparing the self-healing tire in this comparative example includes the following steps: S1. Hydroxyl-terminated polybutadiene-grafted nano-silica was prepared according to the method of Example 1. Based on the measured content of terminal hydroxyl groups, the polybutadiene-grafted nano-silica was divided into a first part and a second part, wherein the terminal hydroxyl groups in the first part accounted for 20% of the total molar number of terminal hydroxyl groups, and the terminal hydroxyl groups in the second part accounted for 80% of the total molar number of terminal hydroxyl groups. 12.51 g of 2-amino-4-hydroxy-6-methylpyrimidine and 111.15 g of isophorone diisocyanate were mixed and reacted at 100°C for 12 h. After precipitation with n-hexane, separation, washing, and drying, an isocyanate-containing ureapyrimidine ketone compound was obtained. The isocyanate-containing ureapyrimidine ketone compound was added to the first part at a molar ratio of isocyanate groups to terminal hydroxyl groups in the first part of 1:1, along with 0.10% (by mass) of dibutyltin dilaurate, and the reaction was carried out at 30°C for 12 h. h, after separation, washing and drying, ureidylpyrimidinone-terminated nano-modified material was obtained; dodecyl isocyanate was added to the second part according to a molar ratio of isocyanate groups in dodecyl isocyanate to terminal hydroxyl groups in the second part of 1:1, and the reaction was carried out at 45℃ for 3 h, after separation, washing and drying, alkyl-blocked-terminated nano-modified material was obtained; the obtained ureidylpyrimidinone-terminated nano-modified material was mixed with the alkyl-blocked-terminated nano-modified material so that the molar ratio of the original terminal hydroxyl groups of the two was 20:80, and a physically compounded nano-modified material was obtained; S2. Weigh 150 g of styrene-isoprene-styrene block copolymer, 200 g of polyisobutylene, 100 g of liquid polyisoprene, 150 g of hydrogenated petroleum resin, 50 g of naphthenic oil, 10 g of physically compounded nano-modified material, and 10102 g of antioxidant; its pre-dispersion and melt compounding operations, as well as the tire inner wall spraying and cooling shaping operations, are all carried out according to Example 1 to obtain a polymer nano-memory rubber-based self-healing tire.
[0026] Performance testing 1. Apparent viscosity at 160℃ The test was conducted using a rotational rheometer with a 25 mm diameter parallel plate as the test fixture and a 1.0 mm test gap. The sample was placed in the test fixture and kept at 160 °C for 5 min. Continuous shear scanning was performed at shear rates from 0.1 to 100 s⁻¹, and the apparent viscosity at a shear rate of 100 s⁻¹ was recorded.
[0027] 2. Structural recovery rate at 60℃ A three-stage thixotropic testing method was adopted. The sample was placed in a rotational rheometer and kept at 60℃ for 5 min before the three-stage thixotropic test was performed.
[0028] In the first stage, the initial viscosity of the sample before shear failure was obtained by testing for 180 s at a shear rate of 0.1 s⁻¹. The second stage involves shearing for 60 s at a shear rate of 100 s⁻¹ to disrupt the physical association structure inside the sample. In the third stage, the shear rate was reduced back to 0.1 s⁻¹, and the test continued for 300 s.
[0029] The average viscosity in the last 30 seconds of the first stage is taken as the initial viscosity, and the average viscosity in the last 30 seconds of the third stage is taken as the recovered viscosity. The structural recovery rate is calculated according to the following formula: Structural recovery rate = recovered viscosity ÷ initial viscosity × 100%.
[0030] 3. High-temperature, high-speed rotation adhesive layer migration rate Each group of standardized coated tires was inflated to 250 kPa. Measurement points were set at the center line and both sides of the self-sealing layer, with 12 points evenly distributed along the circumference of each tire, for a total of 36 measurement points. The initial adhesive layer thickness at each measurement point was determined using a non-contact thickness measuring device, and the positions of the two sides of the adhesive layer were recorded.
[0031] The tires were mounted on a high-speed tire durability testing machine and run continuously for 2 hours at an ambient temperature of 70℃ and a tire speed of 120 km / h. After the test, the tires were allowed to stand at 23±2℃ for 2 hours, and the rubber layer thickness and boundary position at each measurement point were measured again.
[0032] The migration rate of the adhesive layer thickness is calculated using the following formula: Adhesive layer thickness migration rate = average value of absolute difference in thickness before and after the test at each measurement point ÷ average thickness before the test × 100%.
[0033] 4. Pressure retention rate 24 hours after puncture at -20℃ After placing the tire at -20±2℃ for 12 hours, adjust the tire pressure to 250 kPa at this temperature. While keeping the tire in the -20±2℃ environment, use a smooth steel nail with a diameter of 5.0 mm to vertically pierce the tire from the center of the tread, allowing the nail to pass through the tire body and enter the self-sealing layer. After holding for 10 minutes, pull out the nail at a speed of 100 mm / min.
[0034] Three puncture holes were made on each tire, with a minimum distance of 80 mm between adjacent puncture holes. The tire pressure was recorded immediately after nail removal, and then again at 10 min, 1 h, and 24 h after nail removal. The 24-hour tire pressure retention rate was calculated using the following formula: 24-hour tire pressure retention rate = Tire internal pressure 24 hours after nail removal ÷ Tire internal pressure before nail removal × 100%.
[0035] Table 1. Test results of tire core performance
[0036] As shown in Table 1, the apparent viscosity of Examples 1-3 at 160℃ and a shear rate of 100 s⁻¹ is 10.8–14.2 Pa·s, which maintains good high-temperature fluidity and can meet the requirements for heating, conveying and spraying of rubber-based self-sealing materials.
[0037] Compared to Example 1, Comparative Example 1 used unmodified nano-silica, which achieved an apparent viscosity of 13.4 Pa·s at 160°C, but its structural recovery rate at 60°C was only 55.8%, and its adhesive layer migration rate was as high as 17.2%. This result indicates that while unmodified nano-silica can increase the viscosity of the rubber compound through ordinary thickening with fillers, its poor dispersion stability in the non-polar rubber matrix and inability to form an effective reversible structural recovery network prevent it from simultaneously improving the adhesive layer's anti-migration ability and low-temperature pore-sealing performance. Comparative Example 2 used polybutadiene-grafted nano-silica with hydroxyl-terminated ends, which had the lowest apparent viscosity at 160°C at 9.9 Pa·s, indicating that the polybutadiene graft chains can improve the compatibility and high-temperature flowability between the nanoparticles and the rubber matrix; however, due to the absence of ureidopyrimidinone associated end groups and alkyl-closed end groups, its structural recovery rate at 60°C was only 67.4%, and its adhesive layer migration rate was 11.8%, indicating that simply improving particle dispersion and interfacial compatibility is insufficient to form a stable anti-migration structure at tire operating temperatures. Comparative Example 3, which physically blended ureidopyrimidinone-terminated nanoparticles with alkyl-blocked end-group nanoparticles, showed significantly lower structural recovery and anti-migration properties compared to Example 1. The structural recovery rate at 60°C was 76.9%, the adhesive layer migration rate was 8.7%, and the pressure retention rate after 24 hours of low-temperature pore-forming was 94.0%. These results indicate that simply physically mixing two types of single-end-group particles easily leads to localized concentration and uneven spatial distribution of reversible association sites in the adhesive, failing to achieve the same effect as simultaneously setting ureidopyrimidinone-terminated and alkyl-blocked end-groups on the same nanoparticle surface.
[0038] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A method for preparing a self-healing tire based on polymer nano-memory rubber, characterized in that, Includes the following steps: S1. Nano-silica is reacted with aminosilane in an alcohol-water medium to obtain aminated nano-silica; the aminated nano-silica is then reacted with diisocyanate to obtain isocyanate-functionalized nano-silica; hydroxyl-terminated liquid polybutadiene is added to perform a grafting reaction at a molar ratio of (3-6):1 between the hydroxyl groups in the hydroxyl-terminated liquid polybutadiene and the isocyanate groups in the isocyanate-functionalized nano-silica; unreacted hydroxyl-terminated liquid polybutadiene is removed by separation to obtain polybutadiene with hydroxyl-terminated ends. olefin-grafted nano-silica; according to the molar ratio of isocyanate groups to terminal hydroxyl groups in the isocyanate-containing ureapyrimidine ketone compound being (0.20~0.50):1, an isocyanate-containing ureapyrimidine ketone compound is added for reaction, and then according to the molar ratio of isocyanate groups in the alkyl monoisocyanate to the remaining terminal hydroxyl groups after the reaction being (1.0~1.1):1, an alkyl monoisocyanate is added for end-capping reaction, to obtain a mixed-terminal type nano-modified material containing both ureapyrimidine ketone associated end groups and alkyl-capped end groups; S2. The mixed end-group type nano-modified material is added to liquid rubber and part of plasticizer for pre-dispersion to obtain nano-modified pre-dispersion. Then, the nano-modified pre-dispersion is melt-composite with thermoplastic elastomer, polyisobutylene, tackifying resin, remaining plasticizer and antioxidant to obtain rubber-based self-sealing material. S3. Clean and preheat the inner wall of the vulcanized tire, heat the rubber-based self-sealing material to a flowable state, and spray it onto the area of the inner wall of the vulcanized tire corresponding to the tread. S4. Keep the sprayed vulcanized tire rotating and cool it to set, forming a continuous rubber-based self-sealing layer on the inner wall of the vulcanized tire, thus obtaining a polymer nano-memory rubber-based self-healing tire.
2. The method for preparing a polymer nano-memory rubber-based self-healing tire according to claim 1, characterized in that, In S1, the average particle size of the nano-silica is 10–80 nm; the aminosilane is selected from 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane; the mass ratio of the nano-silica to the aminosilane is 100:(3–12); the mass ratio of ethanol to water in the alcohol-water medium is (80–95):(5–20); the pH of the reaction system is 3.5–5.0; the reaction temperature is 60–75 °C; and the reaction time is 3–6 h.
3. The method for preparing a polymer nano-memory rubber-based self-healing tire according to claim 1, characterized in that, In S1, the diisocyanate is selected from one of isophorone diisocyanate, hexamethylene diisocyanate, and dicyclohexylmethane diisocyanate; the molar ratio of the isocyanate group in the diisocyanate to the amino group in the aminated nano silica is (2.2-3.5):1, the reaction temperature is 40-55℃, and the reaction time is 2-4 h.
4. The method for preparing a polymer nano-memory rubber-based self-healing tire according to claim 1, characterized in that, In S1, the number average molecular weight of the hydroxyl-terminated liquid polybutadiene is 1000–5000, and the average hydroxyl functionality is 1.8–2.
6. The grafting reaction is carried out in an anhydrous organic solvent and under a protective atmosphere, at a reaction temperature of 55–75°C, for a reaction time of 8–12 h, and an organotin catalyst of 0.05%–0.30% of the total mass of the reactants in this step is added. After the grafting reaction is completed, the reaction product is washed with butyl acetate to remove unreacted hydroxyl-terminated liquid polybutadiene.
5. The method for preparing a polymer nano-memory rubber-based self-healing tire according to claim 1, characterized in that, In S1, the isocyanate-containing ureidopyrimidinone compound is prepared by reacting 2-amino-4-hydroxy-6-methylpyrimidine with diisocyanate at a molar ratio of 1:(5-8) under a protective atmosphere and at 100-110°C for 12-18 h, followed by precipitation, separation, washing and drying.
6. The method for preparing a polymer nano-memory rubber-based self-healing tire according to claim 1, characterized in that, In step S1, the hydroxyl-terminated polybutadiene-grafted nano-silica reacts with an isocyanate-containing ureidopyrimidinone compound at 30–50°C for 12–24 h, and an organotin catalyst comprising 0.10%–0.50% of the total mass of the reactants in this step is added; the alkyl monoisocyanate is selected from one of n-octyl isocyanate, dodecyl isocyanate, and octadecyl isocyanate, and the end-capping reaction is carried out at a temperature of 45–65°C for a reaction time of 3–6 h.
7. The method for preparing a polymer nano-memory rubber-based self-healing tire according to claim 1, characterized in that, By weight, the raw materials for preparing the rubber-based self-sealing material in S2 include: 15-35 parts of thermoplastic elastomer, 20-45 parts of polyisobutylene, 10-30 parts of liquid rubber, 15-35 parts of tackifying resin, 5-20 parts of plasticizer, 1-6 parts of mixed end-group nano-modified material, and 0.2-1.5 parts of antioxidant; the thermoplastic elastomer is selected from one or two of styrene-isoprene-styrene block copolymer, styrene-butadiene-styrene block copolymer, and styrene-ethylene / butene-styrene block copolymer; the liquid rubber is selected from one of liquid polyisoprene and liquid polybutadiene.
8. The method for preparing a polymer nano-memory rubber-based self-healing tire according to claim 1, characterized in that, The tackifying resin is selected from one or two of hydrogenated petroleum resin, terpene resin, and hydrogenated rosin resin; the plasticizer is selected from one of naphthenic oil and paraffin oil; and the antioxidant is selected from one of hindered phenolic antioxidant and phosphite antioxidant. In S2, the plasticizer used for pre-dispersion accounts for 20% to 50% of the total mass of the plasticizer, the pre-dispersion temperature is 70 to 110°C, and the pre-dispersion time is 15 to 45 min. The melt composite temperature is 120 to 170°C, and the time is 10 to 40 min.
9. The method for preparing a polymer nano-memory rubber-based self-healing tire according to claim 1, characterized in that, In S3, the spraying temperature of the rubber-based self-sealing material is 130-190℃, the preheating temperature of the inner wall of the vulcanized tire is 35-70℃, and the rotation speed of the vulcanized tire during the spraying process is 5-30 r / min; the thickness of the rubber-based self-sealing layer obtained in S4 is 2.0-5.0 mm, and the coverage width is 80%-120% of the designed tread width of the vulcanized tire.